The influence of religiosity and risk taking on cybersex engagement among postgraduate students: a study in Malaysian universities - Hassan, Siti Aishah; Mohd Ayub, Ahmad Fauzi; Ghoroghi, Soudabeh (International Association of Computer Science and Information Technology Press, 2017)
This study attempts to develop a predictive model to enhance the understanding of cybersex by testing hypotheses on the relationships between religiosity, risk taking, and cybersex engagement. Using multistage proportional sampling, 256 postgraduate students who completed an online survey sent to their email addresses were randomly selected from five Malaysian universities. Results provided support for the proposed theoretical model by explaining 22% of variance in endogenous variable. Statistically significant negative relationship was found to exist between religiosity and cybersex engagement. The study also demonstrated a positive significant relationship between risk taking and cybersex engagement. University counselors would do well to be aware, and develop accurate and general knowledge about online sexual activities, address and prevent the probability of it becoming an addiction with serious life consequences for students.